2015
DOI: 10.1159/000381187
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Morphological and Functional Changes after Repeated Intravitreal Dexamethasone Implant (Ozurdex®) for Retinal Vein Occlusion

Abstract: Aims: To evaluate changes in macular morphology and function after repeated intravitreal dexamethasone implant (Ozurdex®) for macular edema (ME) due to retinal vein occlusion (RVO). Methods: Consecutive treatment-naïve patients with ME secondary to RVO were treated with Ozurdex and followed up to 12 months to evaluate functional and morphological outcomes by means of best-corrected visual acuity (BCVA) and microperimetry and by enhanced depth imaging optical coherence tomography, respectively. Results: Thirty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
(27 reference statements)
2
13
0
Order By: Relevance
“…For patients who received a second implant in this study, the mean time between the first and second implant was 155 days (approximately 5 months). This interval is consistent with the interinjection interval of 4.5 months reported in a prospective evaluation of DEX implant in patients with treatment-naïve RVO [21], and with the interinjection interval of 5.6 months reported in the SHASTA study, a large retrospective evaluation in patients with BRVO and CRVO who received at least two DEX implant injections [9]. The mean interval between DEX implant treatments was approximately 5 months (151 days) for patients in the SHASTA study who received no other treatment for RVO-associated ME during the study period [22].…”
Section: Discussionsupporting
confidence: 90%
“…For patients who received a second implant in this study, the mean time between the first and second implant was 155 days (approximately 5 months). This interval is consistent with the interinjection interval of 4.5 months reported in a prospective evaluation of DEX implant in patients with treatment-naïve RVO [21], and with the interinjection interval of 5.6 months reported in the SHASTA study, a large retrospective evaluation in patients with BRVO and CRVO who received at least two DEX implant injections [9]. The mean interval between DEX implant treatments was approximately 5 months (151 days) for patients in the SHASTA study who received no other treatment for RVO-associated ME during the study period [22].…”
Section: Discussionsupporting
confidence: 90%
“…28 Similarly, a recent prospective study of 35 patients indicated that the optimal time for re-treatment for most patients with ME secondary to RVO is <6 months after the first dexamethasone treatment. 29 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, we observed greater fluctuation of mean CSRT in DEX-treated patients than in conjunction with ranibizumab over the entire study period. Previous studies have demonstrated that this factor is a typical feature of repeat DEX treatment in patients with RVO (Bandello et al 2015). However, while BRVO patients who underwent continued treatment with ranibizumab exhibited significantly better outcomes compared to DEX, this difference was no longer statistically significant by the end of the extension trial among patients with CRVO.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have demonstrated that this factor is a typical feature of repeat DEX treatment in patients with RVO (Bandello et al 2015). Patients who received continued treatment with ranibizumab after completing the core study period (COMRADE-B, COMRADE-C) exhibited a sustained improvement in BCVA until month 12, whereas in the DEX-treated patients who entered the extension trial at a lower BCVA level, mean BCVA improved during the first 2 months after retreatment with DEX, but declined thereafter.…”
Section: Discussionmentioning
confidence: 92%